'Vivências partilhadas': Finding common ground in the short stories of three Goan women writers. Issue 3 (January 2019) - Williams, Claire
Abstract : Reference books such as Aleixo Costa's Literatura goesa: apontamentos bibliográficos ['Goan Literature: Bibliographical Notes'] (1967) and Vimala Devi and Manuel de Seabra's Literatura indo-portuguesa ['Indo-Portuguese Literature'] (1971) show that there were relatively few women publishing poetry and fiction in Goa, a Portuguese colony from 1510 until its union with India in 1961. This article focuses on three Goan women writers who were successful in publishing their short stories in newspapers, and later in collections: Monção ['Monsoon'] (1963 ) by Vimala Devi, Tales of Goa (1991) by Berta de Menezes Braganza, and Vivências partilhadas ['Shared Experiences'] (2006 ) by Maria Elsa da Rocha. Each of the women writes with a different agenda, but all of them portray colonial Goa with a critical eye and sensitivity to the lives of women, and the most wretched members of society.